Negotiating Authority Between State Law and Islamic Normativity: A Comparative Socio-Legal Study of Religious Governance in Contemporary Muslim Societies - Wahyu Fitriannor; Nor Fadhila; Ilham Muhajir (Fakultas Syariah UIN Antasari, 2026)
Contemporary Muslim societies face an ongoing tension concerning the legitimacy of authority between state law and Islamic normative systems in regulating religious and family affairs. This dynamic has generated jurisdictional overlaps that challenge legal coherence while simultaneously fostering institutional negotiation rather than absolute dominance by any single authority. Recent developments indicate a shift from rigid dualism toward complex legal pluralism in which state institutions, religious courts, and customary authorities operate concurrently. Such conditions necessitate governance innovations capable of preserving legal certainty and institutional legitimacy through integrative regulatory approaches.This study is grounded in legal pluralism theory, social contract perspectives on state–citizen relations, and authority theory addressing the construction of legitimacy. These frameworks suggest that state law and Islamic normativity are not inherently contradictory but can be harmonized through negotiated institutional arrangements. Critical legal analysis further indicates that authority is shaped through discourse, institutional positioning, and stakeholder interaction rather than existing as a fixed attribute.The research investigates how contemporary Muslim-majority societies negotiate jurisdictional boundaries between state legal systems and Islamic normative frameworks, identifies mechanisms enabling coexistence without hierarchical supremacy, and examines how legitimacy is constructed among competing institutions. It aims to map comparative patterns of authority negotiation across Indonesia, Malaysia, and Aceh, analyze institutional mechanisms that sustain coexistence, and assess outcomes related to justice, legal certainty, and citizen agency.Using a comparative socio-legal methodology, the study analyzes statutory regulations, judicial decisions, and institutional practices across three jurisdictions representing distinct models of legal pluralism. The primary dataset consists of 120 court decisions from religious and state courts issued between 2020 and 2025, supported by institutional documents and secondary scholarship on plural legal systems and state–religion relations.Findings demonstrate that authority negotiation functions through institutional interdependence rather than zero-sum competition. Religious courts exercise shared jurisdiction through mechanisms such as alternative dispute resolution, jurisdictional deference, and coordinated interpretation. State legal frameworks incorporate Islamic normativity through codification, constitutional acknowledgment, and judicial recognition of religious principles. Citizens actively navigate multiple legal forums, selecting institutional venues according to perceived legitimacy and expected outcomes.The study concludes that contemporary Muslim societies can sustain dual legal systems through negotiated authority structures instead of unified hierarchies. Nonetheless, ambiguity remains in jurisdictional boundary areas that require clarification. Policy recommendations include strengthening legislative definitions of jurisdiction, enhancing inter-institutional coordination, improving judicial capacity for managing plural legal systems, and ensuring transparency in forum selection. Recognizing legal pluralism as a structural characteristic rather than a temporary anomaly is essential for effective governance in Muslim-majority contexts.